Silicon-carbon negative electrode material, preparation method and application thereof, and battery
By preparing silicon carbon negative electrode materials, pre-sintering and calcining using a mixture of lithium powder, metal M and silicon powder, the problems of low Coulomb efficiency and poor cycle stability of silicon carbon negative electrode materials are solved for the first time, and higher electrochemical performance and Longer battery life.
Patent Information
- Application Number
- CN202411568888.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-11
AI Technical Summary
The first time the silicon carbon negative electrode material has low efficiency, poor conductivity and poor battery cycle stability, which limits its industrial application.
By performing low-temperature presintering, tableting, and high-temperature sintering of a mixture of lithium powder, metal M (such as Ag and/or Cu) and silicon powder, lithium supplemented materials are obtained and in an inert atmosphere with the inorganic silicon source material and carbon precursor. Calcining and granulation to prepare a silicon-carbon negative electrode material.
This method quickly replenishes lithium during the negative electrode charging and discharging process, improves the first Coulomb efficiency and rate performance of silicon-carbon negative electrode materials, and improves battery cycle stability.
Smart Images

Figure CN119419251A_ABST
Abstract
Description
Technical Field
[0001] The present invention specifically relates to a silicon-carbon negative electrode material and a preparation method, application and battery thereof. Background Art
[0002] Silicon-based anodes are considered to be the next generation of long-life anode materials and a transitional solution for solid-state lithium batteries to achieve lithium metal anodes. Their theoretical specific capacity is 4200mAh / g, which is nearly 12 times that of artificial graphite anodes. However, the first coulombic efficiency of silicon anode materials is much lower than that of graphite anodes, which limits their industrial application. The first coulombic efficiency of pure silicon anode materials is only about 80%, while silicon-oxygen materials will produce irreversible products such as lithium oxide and lithium silicate during the first cycle, and their first coulombic efficiency will drop to 60% to 70%. The reasons include two aspects: (1) Silicon-based anode materials will form irreversible chemical products and solid electrolyte interface (SEI) films during the first charge and discharge cycle, which will cause a significant decrease in the first coulombic efficiency of the battery; (2) During long-term cyclic use, the active material will be deactivated, deposited and shed due to the violent expansion and pulverization of silicon, which will cause the loss of "active lithium" in the battery system.
[0003] In order to solve this problem, the use of lithium supplements is particularly important. Lithium supplements can improve battery cycle stability and improve the first-cycle efficiency by timely replenishing the lithium lost during the cycle. In addition, if the lithium supplement has electronic conductivity and ionic conductivity, it can optimize the electron and ion transmission paths inside the electrode, improve the performance of the overall electrode, improve the rate performance and extend the service life of the battery. The main lithium supplements currently studied include lithium metal compounds such as lithium phosphorus oxide (LiPO) and lithium boron oxide (LiBO), as well as lithium foil and organic lithium compounds. Among them, compounds such as lithium phosphorus oxide have a low lithium content and require a large amount of addition to have a significant improvement effect. Lithium foil and organic lithium compounds have poor stability, which is not conducive to battery safety. Therefore, it is urgent to develop materials with high lithium content, good electrochemical stability and electronic / ionic conductivity as lithium supplements. Summary of the invention
[0004] The technical problem solved by the present invention is to overcome the problems existing in the prior art such as low initial coulombic efficiency, poor conductivity, and poor battery cycle stability of silicon-carbon negative electrode materials, and to provide a silicon-carbon negative electrode material and its preparation method, application, and battery.
[0005] The present invention prepares a silicon-carbon negative electrode material by combining the prepared lithium-supplementing material with an inorganic silicon source material and a carbon precursor. The addition of the lithium-supplementing material can quickly replenish lithium when lithium is irreversibly damaged during the negative electrode charge and discharge process, thereby improving the first coulombic efficiency and rate performance of the silicon-carbon negative electrode material.
[0006] The present invention solves the above technical problems through the following technical solutions:
[0007] The present invention provides a method for preparing a silicon-carbon negative electrode material, which comprises the following steps:
[0008] (1) Pre-sintering a mixture of lithium powder, metal M and silicon powder at low temperature, pressing into tablets, and sintering at high temperature to obtain a lithium supplement material; the metal M is Ag and / or Cu;
[0009] (2) calcining and granulating a mixture containing the lithium supplement material, the inorganic silicon source material and the carbon precursor in an inert atmosphere to obtain the silicon-carbon negative electrode material.
[0010] In step (1), the particle size of the silicon powder may be 0.5-15 μm, preferably 0.5-2 μm.
[0011] In step (1), the molar ratio of the lithium powder, the metal M and the silicon powder may be (12-13):0.75:4, for example, 12.2:0.75:4 or 12.0:0.75:4.
[0012] In step (1), the metal M is preferably Ag.
[0013] In step (1), when the metal M is Ag, the chemical formula of the lithium supplement material is Li 12 Ag 0.75 Si 4 , the crystal structure is Zintl phase.
[0014] In step (1), according to the common practice in the art, the low-temperature pre-sintering and the high-temperature sintering are generally performed under the protection of an inert gas, such as nitrogen or argon.
[0015] In step (1), the temperature of the low-temperature pre-sintering may be 300-400°C, for example 350°C.
[0016] In step (1), the low-temperature pre-sintering time may be 0.5-2 hours, for example, 1 hour.
[0017] In step (1), according to the common practice in the art, grinding is generally required after the low-temperature pre-sintering and before the tableting.
[0018] In step (1), the tabletting pressure is preferably 80-150 MPa, such as 100 MPa.
[0019] In step (1), the high temperature sintering temperature may be 500-800°C, for example 700°C.
[0020] In step (1), the high temperature sintering time may be 2 days to 12 days, preferably 2 days to 5 days, for example 3 days.
[0021] In step (2), the inorganic silicon source material may be one or more of silicon powder, silicon monoxide, silicon dioxide, a silicon-carbon alloy and a silicon-carbon composite material, preferably silicon powder.
[0022] When the inorganic silicon source material is silicon powder, the size of the silicon powder may be 10-200 nm, preferably 50-100 nm.
[0023] In step (2), the carbon precursor may be one or more of asphalt, petroleum coke and phenolic resin, preferably asphalt.
[0024] In step (2), the mass ratio of the inorganic silicon source material to the lithium supplement material may be (10-50):1, preferably (15-35):1, such as 20:1, 25:1 or 30:1.
[0025] In step (2), the mass ratio of the carbon precursor to the lithium supplement material may be (3-20):1, preferably (3-10):1, such as 5:1 or 8:1.
[0026] In step (2), the mixture is preferably ground before calcining. The grinding method can be conventional in the art, such as ball milling. The grinding speed can be 200-500 rpm, such as 300 rpm. The grinding time can be 10-60 min, such as 30 min.
[0027] In step (2), the inert atmosphere may be conventional in the art, such as nitrogen.
[0028] In step (2), the rate of increasing the temperature to the calcination temperature may be 1-5°C / min.
[0029] In step (2), the calcination temperature may be 300-850°C, preferably 300-500°C, for example 400°C.
[0030] In step (2), the calcination time may be 1-10 h, preferably 1-5 h, such as 2 h or 3 h.
[0031] In step (2), before granulation, the sample is generally prepared into a slurry. The solvent in the slurry can be conventional in the art, generally one or more of ethanol, methanol and deionized water, such as ethanol. The solid content of the slurry can be 40-60%, such as 50%. The solid content refers to the ratio of the total mass of solids in the slurry to the total mass of the slurry.
[0032] In step (2), the granulation method is preferably spray granulation. The spray granulation is generally performed in a spray granulator. The process parameters of the spray granulation can be an air inlet temperature of 180-280°C (e.g., 250°C) and an air outlet temperature of 80-140°C (e.g., 120°C).
[0033] The present invention also provides a silicon-carbon negative electrode material prepared by the preparation method as described above.
[0034] The present invention also provides an application of the silicon-carbon negative electrode material as described above in a lithium-ion battery.
[0035] The present invention also provides a lithium-ion battery, which comprises a positive electrode, a negative electrode, an electrolyte and a separator, wherein the negative electrode comprises the silicon-carbon composite material as described above.
[0036] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0037] The reagents and raw materials used in the present invention are commercially available.
[0038] The positive and progressive effects of the present invention are:
[0039] The lithium replenishing material prepared by the present invention has a chemical composition similar to that of silicon, has strong compatibility with silicon negative electrodes, and is not likely to have an adverse effect on the electrochemical performance of the silicon negative electrode when added in large quantities. In addition, this material can achieve stable storage of a large amount of lithium ions through Ag-Si or Cu-Si, Si-Si skeleton structures, and enhances conductivity through silver / copper. By adding it to the silicon negative electrode material, lithium can be quickly replenished when lithium is irreversibly damaged during the negative electrode charge and discharge process, thereby improving the first coulombic efficiency and rate performance of the silicon-carbon negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is the SEM image of the silicon-carbon negative electrode material prepared in Example 1. DETAILED DESCRIPTION
[0041] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0042] The silicon powder used in the following examples and comparative examples was purchased from Aladdin, and had a purity of 99.9% and a particle size of 1 μm.
[0043] Example 1
[0044] (1) After mixing metallic silver powder, lithium powder and silicon powder in a molar ratio of 0.75:12:4, the mixture is placed in a crucible and heated to 350°C at a heating rate of 2°C / min in a nitrogen-protected tubular furnace, pre-sintered for 1 hour, ground into powder after cooling, pressed into tablets with a powder tablet press at 100 MPa, and then heated to 700°C at a heating rate of 2°C / min in a nitrogen-protected tubular furnace, maintained at the temperature for 3 days, and cooled to obtain a lithium supplement material;
[0045] (2) The lithium supplement material obtained in step (1), nano silicon powder (80-100 nm, Colod), and asphalt are mixed in a mass ratio of 1:20:5, and ball milled at 300 rpm for 30 minutes using a planetary ball mill. The mixture is heated to 400°C at a heating rate of 3°C / min in a nitrogen-protected tubular furnace and maintained for 2 hours. After cooling, the sample is dispersed in an ethanol solvent to prepare a slurry with a solid content of 50 wt%. The slurry is pumped into a spray granulator for spray granulation at an air inlet temperature of 250°C and an air outlet temperature of 120°C to obtain a silicon-carbon negative electrode material.
[0046] Example 2
[0047] Compared with Example 1, except that the metal silver powder in step (1) is changed to metal copper powder, the other parameters and conditions are the same as those in Example 1.
[0048] Example 3
[0049] Compared with Example 1, except that the nano silicon powder in step (2) is replaced with silicon dioxide (model 1600, CLUDE, D 50 Except for the thickness of 5.012 μm, the other parameters and conditions are the same as those in Example 1.
[0050] Example 4
[0051] Compared with Example 1, except that the nano-silicon powder in step (2) is replaced by a silicon-carbon negative electrode (model 1800, porous carbon deposition, Colotech, D 50 Except for the thickness of 8.198 μm, the other parameters and conditions are the same as those in Example 1.
[0052] Example 5
[0053] Compared with Example 1, except that the nano silicon powder in step (2) is replaced by silicon carbon alloy (model 1200, Kelude, D 50 Except for the thickness of 14.502 μm, the other parameters and conditions are the same as those in Example 1.
[0054] Example 6
[0055] Compared with Example 1, except that the mass ratio of lithium supplement material, nano silicon powder and asphalt in step (2) is adjusted to 1:30:5, the other parameters and conditions are the same as those in Example 1.
[0056] Example 7
[0057] Compared with Example 1, the asphalt in step (2) is replaced by phenolic resin (brand BOSF, F0303 type).
[0058] Comparative Example 1
[0059] Nano silicon (80-100nm, CROOD).
[0060] Comparative Example 2
[0061] Silicon dioxide (Model 1600, CLUDE, D 50 is 5.012μm).
[0062] Comparative Example 3
[0063] Silicon carbon anode (Model 1800, porous carbon deposition, CLUDE, D 50 is 8.198μm).
[0064] Comparative Example 4
[0065] Silicon carbon alloy (Model 1200, CLUDE, D 50 is 14.502μm).
[0066] Effect Example
[0067] (1) Morphological characterization
[0068] Figure 1 This is the SEM image of the silicon-carbon negative electrode material prepared in Example 1.
[0069] (2) Electrochemical performance test
[0070] The silicon-carbon negative electrode materials prepared in Examples 1 to 7 and the silicon negative electrode materials in Comparative Examples 1-4 were subjected to half-cell tests. The test method is: the above materials are uniformly mixed with a binder CMC (sodium carboxymethyl cellulose) and conductive carbon black at a mass ratio of 80:10:10, adjusted into a slurry, coated on a copper foil with a coating thickness of 100 microns, and dried at 80°C in vacuum for 12 hours to prepare a lithium battery negative electrode sheet. The simulated battery assembly was carried out in an argon-filled glove box, using 1 mol / L LiPF 6The electrolyte (solvent is EC, DMC and FEC, EC:DMC=1:1 (volume ratio), FEC accounts for 5% of the total volume of the solvent), a polypropylene microporous membrane is used as a separator, and a metal lithium sheet positive electrode is used as a counter electrode. The electrochemical performance test was carried out on a Land CT2001A battery tester at a temperature of 25°C and a charge and discharge voltage range of 0.01 to 1.5V (1C=1500mAh g -1 ). The test results are shown in Table 2.
[0071] Table 2
[0072]
[0073]
[0074] According to the above experimental results, the high first-efficiency silicon-carbon negative electrode material prepared in the present invention has excellent electrochemical properties, especially the first coulombic efficiency and cycle life.
[0075] In Comparative Examples 1-4, various silicon-containing negative electrode materials will consume part of the lithium during the first charge of the battery due to the formation of the solid electrolyte membrane (SEI membrane), resulting in the loss of lithium in the positive electrode material. Without lithium replenishment, the capacity and initial efficiency of the battery are reduced.
[0076] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A method for preparing a silicon-carbon negative electrode material, characterized in that: The following steps are involved: (1) Pre-sintering a mixture of lithium powder, metal M and silicon powder at low temperature, pressing into tablets, and sintering at high temperature to obtain a lithium supplement material; the metal M is Ag and / or Cu; (2) calcining and granulating a mixture containing the lithium supplement material, the inorganic silicon source material and the carbon precursor in an inert atmosphere to obtain the silicon-carbon negative electrode material.
2. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: In step (1), the molar ratio of the lithium powder, the metal M and the silicon powder is (12-13):0.75:4, for example, 12.2:0.75:4 or 12.0:0.75:4; And / or, the particle size of the silicon powder is 0.5-15 μm, preferably 0.5-2 μm.
3. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: In step (1), the temperature of the low-temperature pre-sintering is 300-400° C., for example, 350° C.; And / or, in step (1), the low temperature pre-sintering time is 0.5-2h, for example 1h; And / or, in step (1), the tabletting pressure is 80-150 MPa, for example 100 MPa.
4. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: In step (1), the high temperature sintering temperature is 500-800° C., for example, 700° C.; And / or, in step (1), the high temperature sintering time is 2 days to 12 days, preferably 2 days to 5 days, for example 3 days.
5. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: Step (2) satisfies one or more of the following conditions: (1) The inorganic silicon source material is one or more of silicon powder, silicon monoxide, silicon dioxide, silicon-carbon alloy and silicon-carbon composite material, preferably silicon powder; (2) The carbon precursor is one or more of asphalt, petroleum coke and phenolic resin, preferably asphalt; (3) The mass ratio of the inorganic silicon source material to the lithium supplement material is (10-50):1, preferably (15-35):1, for example 20:1, 25:1 or 30:1; (4) The mass ratio of the carbon precursor to the lithium supplement material is (3-20):1, preferably (3-10):1, for example 5:1 or 8:
1.
6. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: In step (2), the calcination temperature is 300-850°C, preferably 300-500°C, for example 400°C; And / or, in step (2), the calcination time is 1-10 h, preferably 1-5 h, such as 2 h or 3 h.
7. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: In step (2), before granulation, the sample needs to be made into a slurry; the solvent in the slurry is preferably one or more of ethanol, methanol and deionized water; the solid content of the slurry is preferably 40-60%, for example 50%; And / or, in step (2), the granulation is spray granulation; the process parameters of the spray granulation are preferably an air inlet temperature of 180-280°C and an air outlet temperature of 80-140°C.
8. A silicon-carbon negative electrode material, characterized in that: The silicon-carbon composite material is prepared according to the method for preparing the silicon-carbon composite material as described in any one of claims 1 to 7.
9. Use of the silicon-carbon negative electrode material as claimed in claim 8 in a lithium-ion battery.
10. A lithium ion battery, characterized in that: It comprises a positive electrode, a negative electrode, an electrolyte and a separator, wherein the negative electrode comprises the silicon-carbon negative electrode material as claimed in claim 8.
Citation Information
Cited By
Silicon-carbon negative electrode material, preparation method and application thereof, and lithium ion battery
CN119660747A
A silicon-carbon negative electrode material, a preparation method thereof, an application thereof, and a lithium-ion battery
CN119660747B